The Strengths and Weaknesses of Cooperative Learning and Problem-Based Learning in EFL Writing Class: Teachers’ and Students’ Perspectives - Ghufron, M. Ali; Ermawati, Siti (International Journal of Instruction, 2018)
This study was aimed at evaluating the strengths and weaknesses of cooperative learning and problem-based learning in EFL writing classes. This study employed a case study method. The respondents of the research were 2 EFL writing teachers and 60 students who took EFL writing course in English Education Department of a private university in East Java, Indonesia. The respondents were chosen based on purposive sampling technique. The data was gained through questionnaires, in-depth interview, and observation. After analyzing the data descriptively, the results show that raising student' self-confidence and motivation, reducing students' nervousness, raising students' responsibility in learning, and making the students easier to learn are the strengths of Cooperative Learning (CL). On the other hand, the weaknesses of CL are that it needs much more time to implement, it needs active participation from both teachers and students, it is difficult to manage, and it needs more preparation. While in Problem-based Learning (PBL), problem solving skills, self-directed learning skills, reducing students' nervousness, raising student' self-confidence and motivation, raising students' responsibility in learning, easily sharing and exchanging ideas among students, making the students more active in learning, making the students explore many learning sources to solve the problems, and making the students have positive attitude to learning were classified into the strengths of PBL.